Strategi Digital Marketing sebagai Media Komunikasi Pemasaran Paket Umrah pada PT Adhiya Wisata Utama Bandung - Fauziah, Hilma Mulqiyah; Hilman, Fathin Anjani (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
This study aims to find out the management of marketing, and the impact of marketing strategies through digital marketing on PT. Adhiya Wisata Utama. The research method used is descriptive in a qualitative approach using Kotler's marketing strategy theory. The results of the study show that PT. Adhiya Wisata Utama implements a marketing strategy in the form of market segmentation through the grouping of tour packages by empowering employee experience to offer packages to the public in accordance with the market segmentation that has been determined, and the impact of this strategy, which is to produce an increase in the interest of prospective Umrah pilgrims, as evidenced by the increasing frequency of Umrah pilgrim departures.